In vitro and ex vivo screening of microRNA combinations with enhanced cell penetrating peptides to stimulate intervertebral disc regeneration - Buckley, Conor (My University, 2024)
Background: Low back pain (LBP) is predominantly caused by degeneration of the intervertebral disc (IVD) and central nucleus pulposus (NP) region. Conservative treatments fail to restore disc function, motivating the exploration of nucleic acid therapies, such as the use of microRNAs (miRNAs). miRNAs have the potential to modulate expression of discogenic factors, while silencing the catabolic cascade associated with degeneration. To deliver these miRNAs, nonviral cell penetrating peptides (CPPs) are gaining favor given their low immunogenicity and strong targeting ability. Single miRNA therapies have been investigated for IVD repair, however dual miRNA delivery strategies have not been commonly examined and may augment regeneration. Materials and methods: Transfection of four pro-discogenic miRNAs (miRNA mimics:140-5p; 149-5p and inhibitors: 141-3p; 221-3p) and dual delivery of six miRNA pairings was performed using two CPPs, RALA and GET peptide (FLR), in primary rat NP monolayer culture, and in an ex vivo organ culture model of rat caudal discs. Protein expression of discogenic (aggrecan, collagen type II, and SOX9) and catabolic markers (ADAMTS5 and MMP13) were assessed. Results: Monolayer investigations signified enhanced discogenic marker expression following dual miRNA delivery, signifying a synergistic effect when compared to single miRNA transfection. Utilization of an appropriate model was emphasized in our ex vivo organ culture experiment, revealing the establishment of a regenerative microenvironment characterized by reduced catabolic enzyme activity and enhanced matrix deposition, particularly following concurrent delivery of FLR-miRNA-149-5p mimic and miRNA-221-3p inhibitor. Bioinformatics analysis of miRNA-149-5p mimic and miRNA-221-3p inhibitor identified distinct targets, pathways, and interactions, suggesting a mode of action for this amplified response. Conclusion: Our findings suggest the potential of FLR-miRNA-149-5p + miRNA-221-3p inhibitor to create an anti-catabolic niche within the disc to foster regeneration in moderate cases of disc degeneration, which could be utilized in further studies with the overarching aim of developing treatments for LBP.
PUBLISHED
Keywords: anti‐catabolism; cell penetrating peptides; cell therapies; microRNA; regeneration